Studi Eksperimen Pengaruh Penambahan Serabut Kelapa Terhadap Kohesi dan Sudut Geser Tanah Lempung - Pebrinar Sangle (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
This research is intended to study the shear strength of clay soil before and after adding coconut fibers. Shear strength is one of the factors that are taken into account to find the bearing capacity of the soil. Soil stability is a way to improve or change the nature of an unfavorable subgrade condition to be better in terms of the bearing capacity of the subgrade for the construction to be built on its Strength parameter testing shear using direct shear test equipment with total stress conditions. This research used coconut fiber variations of 0%, 1%, 2%, 3%, and 4% of the dry weight of the soil. The results of the direct shear test showed an increase in the value of soil cohesion (c) and shear angle (φ). This shows that the addition of coconut fibers to clay soil can increase the value of shear strength.